2019
DOI: 10.3390/ijms20020435
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Fabrication of Biomaterials for Bone and Cartilage Regeneration: Materials Modifications and Biophysical Stimulations

Abstract: The aim of engineering of biomaterials is to fabricate implantable biocompatible scaffold that would accelerate regeneration of the tissue and ideally protect the wound against biodevice-related infections, which may cause prolonged inflammation and biomaterial failure. To obtain antimicrobial and highly biocompatible scaffolds promoting cell adhesion and growth, materials scientists are still searching for novel modifications of biomaterials. This review presents current trends in the field of engineering of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 123 publications
0
58
0
Order By: Relevance
“…The organic part of biomaterial provides biomaterial flexibility and improves its biocompatibility [21][22][23], whereas the inorganic part provides load-bearing strength and stiffness [22]. In organic-inorganic composites, the organic matrix may be composed of natural polymers (e.g., chitosan, collagen, hyaluronic acid, fibrin, silk fibroin, alginate, amylopectin, carrageenan, agar, dextran, xanthan gum, pullulan) [15,[23][24][25][26] and/or synthetic polymers (e.g., polylactic acid (PLA), polycaprolactone (PCL), poly(glycolic acid) (PGA), polyanhydride, polyphosphazene, polyether ether ketone (PEEK), polypropylene fumarate (PPF)) [27], whereas the inorganic part may be made of metal alloys [16] and ceramics, such as hydroxyapatite (HA), calcium phosphate bone cements (CPS), α-tricalcium phosphate (α-TCP), β-tricalcium phosphate (β-TCP), Bioglass (BG), glass-ceramics, as well as carbon nanotubes [15,24,27,28].…”
Section: Bone Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…The organic part of biomaterial provides biomaterial flexibility and improves its biocompatibility [21][22][23], whereas the inorganic part provides load-bearing strength and stiffness [22]. In organic-inorganic composites, the organic matrix may be composed of natural polymers (e.g., chitosan, collagen, hyaluronic acid, fibrin, silk fibroin, alginate, amylopectin, carrageenan, agar, dextran, xanthan gum, pullulan) [15,[23][24][25][26] and/or synthetic polymers (e.g., polylactic acid (PLA), polycaprolactone (PCL), poly(glycolic acid) (PGA), polyanhydride, polyphosphazene, polyether ether ketone (PEEK), polypropylene fumarate (PPF)) [27], whereas the inorganic part may be made of metal alloys [16] and ceramics, such as hydroxyapatite (HA), calcium phosphate bone cements (CPS), α-tricalcium phosphate (α-TCP), β-tricalcium phosphate (β-TCP), Bioglass (BG), glass-ceramics, as well as carbon nanotubes [15,24,27,28].…”
Section: Bone Regenerative Medicinementioning
confidence: 99%
“…Moreover, the piezoelectric biomaterials may generate a bioelectrical signal influenced by mechanical stress exposure, that may mimic the stress-generated potentials of natural bone. This type of biomaterials may also be subjected to electrical stimulation or ultrasound to promote bone healing [25]. Fan et al [46] used BaTiO 3 to modify the surface of Ti scaffold.…”
Section: Inorganic and Composite Coatingsmentioning
confidence: 99%
“…Scaffolds are useful substrates to study the effect of plasma-derived ROS on growth and invasion of cancer cells. Previous studies have shown that plasma can change the biophysical properties of polymers, as it can enhance the polymerization and biophysical stimulation of biomaterials used for bone and cartilage regeneration [290,291]. Thus, it could be expected that plasma would oxidize or modify the properties of these scaffolds in 3D cultures, therefore providing relevant information about the effect of plasma on the ECM and cells of the TME under oxidative stress.…”
Section: Scaffoldsmentioning
confidence: 99%
“…In the field of biomaterials engineering, cold plasma technology is primarily used for surface functionalization with hydrophilic chemical groups to enhance cell adhesion and proliferation on the implants [ 10 ]. Atmospheric pressure plasma is also used to improve surface properties of the biomaterials, especially wettability and roughness that are known to significantly influence biocompatibility of the implants [ 11 , 12 ]. Materials scientists frequently use atmospheric pressure plasma combined with oxygen, argon, air, ammonia, or nitrogen gas for biocompatibility improvement of various polymeric biomaterials [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%